Potentiometric measurement of entropy change for lithium batteries. Issue 15 (10th March 2017) - Zhang, Xiao-Feng; Zhao, Yan; Patel, Yatish; Zhang, Teng; Liu, Wei-Ming; Chen, Mu; Offer, Gregory J.; Yan, Yue
Abstract : Entropy change can be employed to track battery degradation compared with EIS and CV. Abstract : Effective thermal management and tracking of battery degradation are two key challenges in the improved management of battery packs. Entropy change measurement is a non-destructive tool for characterizing both the thermal and structural properties of lithium batteries. However, conventional entropy measurements based on discontinuous potentiometric methods are too time-consuming for practical implementation in battery packs. We present a comprehensive review of potentiometric methods for the entropy change measurement of lithium batteries. We compare conventional and improved discontinuous methods as well as a fully continuous method. Entropy measurements were then made using all the techniques for a solid-state microbattery using a bespoke test system utilising Peltier elements for rapid temperature control. The trade-off between accuracy and speed for the different methods is discussed in detail. In conclusion, the improved discontinuous measurement with significantly reduced voltage relaxation time is recommended for the determination of entropy change during the lithiation/delithiation intercalation reaction in lithium batteries.